INTEGRASI PENDIDIKAN KARAKTER ISLAMI DAN NILAI-NILAI HUKUM ISLAM: TELAAH LITERATUR TERHADAP PENDEKATAN PEMBELAJARAN HOLISTIK - Alfan Nasrullah, Achmad Muzammil; Muin, Abdul; Rosyid, Moh. Zaiful; Mahrus; Elman, Moh. (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze the integration of Islamic character education with Islamic legal values in holistic learning context as response to educational system fragmentation separating religious aspects from practical application. Moral degradation in globalization era demands character education revitalization integrating fundamental Islamic law values as foundation for noble morals formation. Research employs qualitative paradigm with library research approach, analyzing literature through thematic analysis to identify integration patterns and key concepts. Results indicate integration can be implemented through three models: integrative thematic approach, experiential learning, and collaborative learning emphasizing direct experience and contextual problem-solving. Theoretical framework integrates ontological, epistemological, and axiological components in four levels: philosophical, theoretical, methodological, and practical with maqashid al-syariah principles as evaluation foundation. Research contributes to developing Islamic education models responsive to contemporary challenges while maintaining authentic Islamic identity, producing graduates with excellent character and deep Islamic law understanding for civil society formation.